Supervisi Klinis Sebagai Instrumen Perubahan dalam Manajemen Pendidikan Islam - Imamah, Istianatul; Rofiq, Ainur (Journal of Education Management Research, 2024)
This study aims to apply clinical supervision as an instrument of change in Islamic education management. The research object of the discussion of Clinical Supervision as an Instrument of Change in Islamic Education Management is Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi. The design of this study uses a type of qualitative research with a case study approach, which aims to explore the phenomenon of clinical supervision as an instrument of change in Islamic education management at Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi. The sources of informants in this study are the principal, teachers, and quality assurance team at Madrasah Aliyah Blokagung Banyuwangi East Java because they have a key role in the implementation of clinical supervision and changes in education management. The data collection techniques in this study were observation, interviews, and documents because these three methods complement each other to provide an in-depth understanding of the implementation of clinical supervision at Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi. The data analysis technique in this study uses the Milles and Huberman model including, data reduction, data presentation, and conclusion drawing. The results of this discussion are about clinical supervision as an instrument of change in Islamic education management including strengthening teacher skills, innovation in teaching practice, and changes in management policies.